Factors Associated with Food Insecurity in Latin America and the Caribbean Countries: A Cross-Sectional Analysis of 13 Countries - Hernández-Vásquez, Akram (2022)
It is estimated that Latin America and the Caribbean (LAC) is the region with the second highest figures for food insecurity (FI) globally, with a prevalence of 40.9% in the entire region. This cross-sectional study analyzes the household factors associated with FI across 13 LAC countries. We used data from the first round of high-frequency phone surveys, conducted by the World Bank. Approximately 4 out of 10 people in LAC experienced FI during the first phase of the COVID-19 pandemic. FI was positively associated with the number of individuals aged from 5 to 18 years, the number of men, the illness, accident, or death of an income-earning household member, and health expenditure due to COVID-19 or other illnesses, as well as the increase in food prices, reduced family income, and job loss by a member of the household. On the other hand, households located in capital cities and those with more bedrooms were less likely to have experienced FI. The design of social policies must focus on the economic deficiencies experienced by the LAC population, with unemployment, reduced income, and high food costs being the main factors that must be addressed to ensure adequate nutrition.